"Lest We Forget": A Postapartheid Perspective on Remembering in Liturgy for Healing and Justice. (March 2021) - Scott, Hilton
The idea of Remembrance Day (also known as Armistice Day) in the United Kingdom and Commonwealth countries carries two important notions: (1) to remember significant tragedies and sacrifices of the past by paying homage, and (2) to ensure that such catastrophes are prevented in the future by not forgetting. This concept can be applied to the South African context of a society and young democracy that is living in the wake of apartheid. In certain spheres this will include decolonizing the long-standing practices of Remembrance Day in South Africa, ritualizing the event(s) to be more relevant to those who partake by shifting the focus to tragedies caused during apartheid, and remembering that such a deplorable catastrophe should never be repeated. The important liturgical functions and pragmatic outcome(s) of this notion are reconciliation, restoration, transformation and, ultimately, liberation, as South Africans look to heal the wounds caused by the tragedies of the recent past and prevent such pain from being inflicted on others in the future.